Amplified pathogenic actions of angiotensin II in cysteine‐rich LIM‐only protein 4–negative mouse hearts. Issue 4 (30th January 2017) - Straubinger, Julia; Boldt, Karsten; Kuret, Anna; Deng, Lisa; Krattenmacher, Diana; Bork, Nadja; Desch, Matthias; Feil, Robert; Feil, Susanne; Nemer, Mona; Ueffing, Marius; Ruth, Peter; et al.
Abstract : LIM domain proteins have been identified as essential modulators of cardiac biology and pathology; however, it is unclear which role the cysteine‐rich LIM‐only protein (CRP)4 plays in these processes. In studying CRP4 mutant mice, we found that their hearts developed normally, but lack of CRP4 exaggerated multiple parameters of the cardiac stress response to the neurohormone angiotensin II (Ang II). Aiming to dissect the molecular details, we found a link between CRP4 and the cardioprotective cGMP pathway, as well as a multiprotein complex comprising well‐known hypertrophy‐associated factors. S ignificant enrichment of the cysteine‐rich intestinal protein (CRIP)1 in murine hearts lacking CRP4, as well as severe cardiac defects and premature death of CRIP1 and CRP4 morphant zebrafish embryos, further support the notion that depleting CRP4 is incompatible with a proper cardiac development and function. Together, amplified Ang II signaling identified CRP4 as a novel antiremodeling factor regulated, at least to some extent, by cardiac cGMP. —Straubinger, J., Boldt, K., Kuret, A., Deng, L., Krattenmacher, D., Bork, N., Desch, M., Feil, R., Feil, S., Nemer, M., Ueffing, M., Ruth, P., Just, S., Lukowski, R. Amplified pathogenic actions of angio‐tensin II in cysteine‐rich LIM‐only protein 4 negative mouse hearts. FASEB J . 31, 1620–1638 (2017) www.fasebj.org